Hubungan Persepsi Dengan Perilaku Ibu Dalam Persiapan Masa Pubertas Pada Pra Remaja - Chuzaini, Ananda Putri Nida'ul; Mustafa, Annasari; Kundarti, Finti Isti; Toyibah, Afnani (Madu Jurnal Ilmu Kebidanan, 2025)
Puberty is a critical phase in a child’s development requiring physical, psychological, and social readiness. Mothers, as primary caregivers, play an important role in accompanying and providing education during this transition. Inaccurate perceptions by mothers may affect the quality of their supportive behavior. This study aims to examine the relationship between mothers’ perception and behavior in preparing children for puberty. This analytic observational study used a cross-sectional design. The sample consisted of 45 mothers with preadolescent children at MI Sunan Kalijaga Mergan, Malang City, selected by purposive sampling. Perception data were collected using a Likert scale questionnaire (1–4), while behavior was measured through narrative observation sheets. Data were analyzed using Spearman’s correlation test. Results showed that most respondents had positive (55.6%) and moderate (37.8%) perception categories, and behaviors in moderate (62.2%) and good (31.1%) categories. Statistical analysis revealed a significant relationship between perception and behavior (p = 0.002; r = 0.455). The more positive the mother’s perception, the better the supportive behavior. These findings emphasize the importance of improving mothers’ perceptions through appropriate education to enhance supportive behavior during their children’s puberty transition.